Innate Immune Signaling in the Pathogenesis of Necrotizing Enterocolitis. (23rd May 2013) - Hackam, David J.; Afrazi, Amin; Good, Misty; Sodhi, Chhinder P.
Abstract : Necrotizing enterocolitis (NEC) is a challenging disease to treat, and caring for patients afflicted by it remains both frustrating and difficult. While NEC may develop quickly and without warning, it may also develop slowly, insidiously, and appear to take the caregiver by surprise. In seeking to understand the molecular and cellular processes that lead to NEC development, we have identified a critical role for the receptor for bacterial lipopolysaccharide (LPS) toll like receptor 4 (TLR4) in the pathogenesis of NEC, as its activation within the intestinal epithelium of the premature infant leads to mucosal injury and reduced epithelial repair. The expression and function of TLR4 were found to be particularly elevated within the intestinal mucosa of the premature as compared with the full-term infant, predisposing to NEC development. Importantly, factors within both the enterocyte itself, such as heat shock protein 70 (Hsp70), and in the extracellular environment, such as amniotic fluid, can curtail the extent of TLR4 signaling and reduce the propensity for NEC development. This review will highlight the critical TLR4-mediated steps that lead to NEC development, with a focus on the proinflammatory responses of TLR4 signaling that have such devastating consequences in the premature host.